Indian castor oil exports concentration- a perspective: Indian castor oil exports concentration- a perspective - N SANDRA; C SARADA; N K CHAURE (Journal of Oilseeds Research, 2020)
India is the global leader and ranks first in production with almost 87 percent of world’s share as well as in exports of castor oil with a share of 86.8 percent of world’strade (2018-19) and the export is valued at ` 5658 crores. Geographic concentration was analyzed using Herfindahl-Hirschman Index (HHI). It showed that the exports are highly concentrated ranging from 2032 to 2584 for the last eight years except for the year 2014-15 when it was 1668 (moderate concentration).The analysisrevealed thatthe castor oil export destinations are highlyconcentrated to only 10 countries. However, diversification of markets is always desirable